Comparative study on microbial and botanical pesticides as biorational control of mango hopper - Rahman, Md Sohanur; Rahman, Md Arifur; Mia, Md Mukul; Jahan, Mahbuba (Asian Journal of Medical and Biological Research, 2020)
Mango hopper is considered as one of the most destructive pests of mango in Bangladesh which can be effectively controlled by using bio-agents and botanical pesticides. An experiment was conducted at the IPM Laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh, Bangladesh to study the comparative performance of three botanicals (Neem, Mahogany and Karanja oils) and a microbial pesticides (Beauveria bassiana) for the management of mango hopper (Idioscopus clypealis). The experiment was designed following completely randomized design (CRD) using 39 petridishes of 12 cm in diameter. Four insecticides each with 3 different doses (1%, 2% and 3%) were evaluated for their effectiveness. The data on the number of hopper killed were collected every day of a week. Results showed that all the three doses of Beauveria bassiana effectively controlled mango hopper. All the treatments influenced significantly in the management of mango hopper in comparison to the control. Among the botanicals 3% Neem oil was the most effective best but relatively lower performance was observed in case of 1% Mahogany oil. Observation on the effect of a microbial pesticide (Beauveria bassiana) and some botanicals on the infestation of mango hopper at different stages showed that hopper population at pea-shaped after prior to the second spray was maximum in 1% Mahogany oil (13.87) and minimum number of hopper was found in 3% Beauveria bassiana (7.33). Overall results suggested that Beauveria bassiana as a microbial pesticide performed better than botanicals in controlling mango hopper and resulting in higher yield. Asian J. Med. Biol. Res. June 2019, 5(4): 330-335